USING PLANETSCOPE SATELLITE IMAGERY TO QUANTIFY SHORELINE AND SANDBAR DYNAMICS OF THE GAM RIVER SECTION FLOWING XUAN VAN COMMUNE, TUYEN QUANG PROVINCE - Thi Phuong Thao, Vu; Phi Hung, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
Shoreline and sandbar dynamics directly reflect the morpho-sedimentary equilibrium of fluvial systems. This study employs 3-m resolution PlanetScope satellite imagery integrated with Geographic Information Systems (GIS) to analyse shoreline and sandbar changes along the Gam River section flowing through Xuan Van commune, Tuyen Quang province, during the period 2015-2024. Shoreline and sandbar boundaries were delineated through visual interpretation and manual digitization of multi-temporal PlanetScope imagery in a GIS environment, enabling quantitative assessment of erosion, deposition, and channel migration during 2015-2024. The results indicate that during this ten-year period. The results indicate that during 2015-2019, shoreline displacement was limited (ranging from 10-80 m), with relatively balanced erosion and deposition processes, reflecting a stable morphological condition. From 2019 onward, the shoreline changed significantly, with several areas shifting by more than 300 m. The eroded area markedly surpasses the deposited area, indicating a clear trend toward morphological instability. These changes are closely associated with sandbar dynamics, the meandering river planform, and increasing anthropogenic pressures in the study area. The study confirms that PlanetScope imagery is an effective data source for detecting rapid, reach-scale riverine geomorphic changes and provides quantitative evidence to support river management and erosion mitigation strategies.